2018
DOI: 10.1002/jcb.26678
|View full text |Cite
|
Sign up to set email alerts
|

MIAT lncRNA is overexpressed in breast cancer and its inhibition triggers senescence and G1 arrest in MCF7 cell line

Abstract: Long non-coding RNAs are known as key regulators in the progression and metastasis of breast cancer. MIAT originally has been considered as an lncRNA to be associated with a susceptibility to myocardial infarction. Here, we have detected the expression of MIAT in different cancer cells and a series of breast tumor tissue. MIAT expression was much higher in high-grade tumors compared to low-grade ones. Unlike P53 positive tumors, MIAT expression was upregulated in ER, PR, Her2 positive tumor tissues. Knockdown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 22 publications
3
58
1
Order By: Relevance
“…Studies have shown that the decline in yeast cell proliferation caused by aging and cell death is associated with G1/S phase transition disorders (22). Decreased cell proliferation levels and G1 phase cell arrest were also observed in senescent breast cancer cells (23). These studies suggest that the blockade of the G1/S phase transition and decreased cell proliferation levels are among the hallmarks of cellular senescence.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Studies have shown that the decline in yeast cell proliferation caused by aging and cell death is associated with G1/S phase transition disorders (22). Decreased cell proliferation levels and G1 phase cell arrest were also observed in senescent breast cancer cells (23). These studies suggest that the blockade of the G1/S phase transition and decreased cell proliferation levels are among the hallmarks of cellular senescence.…”
Section: Discussionmentioning
confidence: 88%
“…These studies suggest that the blockade of the G1/S phase transition and decreased cell proliferation levels are among the hallmarks of cellular senescence. In addition to cell cycle transformation disorders, increased expression of the cell senescence marker p16 can be observed (23). Previous studies have suggested that p16 inhibits function of cyclin-dependent kinases, causing G1 cell cycle arrest (18).…”
Section: Discussionmentioning
confidence: 99%
“…was recently found to be up-regulated in ER-positive BC tissues. 57,58 MIAT silencing in MCF-7 cells decreased cell proliferation while its overexpression increased MCF-7 cell proliferation. MIAT expression was critical for G1 to S-phase cell cycle transition.…”
Section: Lncrnas With Functional Rolesmentioning
confidence: 92%
“…The lncRNA myocardial infarction associated transcript (MIAT) was recently found to be up‐regulated in ER‐positive BC tissues . MIAT silencing in MCF‐7 cells decreased cell proliferation while its overexpression increased MCF‐7 cell proliferation.…”
Section: Lncrnas and Estrogen‐positive Subtypesmentioning
confidence: 99%
“…MIAT is also disrupted in a number of cancer cell lines, and is expressed at significantly lower levels in grade I-II breast tumors, as compared to those considered high grade III-IV tumors [110] . MIAT also modulates the invasive capacities of breast cancer cells by mediating the ncRNA interaction networks between ZEB1 and certain miRNAs, such as miR-150 and miR-29 [173] . For instance, knockdown of MIAT promotes the expression of miR-150, yet also results in the reduction of miR-29 levels.…”
Section: Myocardial Infarction Associated Transcriptmentioning
confidence: 99%